Facilitating Second Language Acquisition Through Computer Assisted Language Learning - Cobb, Kimberly J. (Valdosta State University College of Education, 2002)
This paper discusses an action research project that explores the experiences of both, teachers and students, who used computer assisted language learning (CALL) to facilitate second language acquisition with ESOL students. Nine students enrolled in an ESOL 10th grade English class participated in this study. Module scores, field notes on dialog/conversation, and teachers' reports showed that the ESOL students made progress in their acquisition of the English language after approximately five weeks of instruction and favorable reports were given regarding the role of CALL in that instruction. It was concluded that computer assisted language learning can enhance students' motivation and confidence in using the English language and can assist with language acquisition in ESOL students.